PERAN IBU SINGLE PARENT DALAM PENGASUHAN ANAK - Andi Tahir (AN-NISA, 2025)
This study aims to describe the role of single mothers in childcare and the challenges they face in carrying out family functions independently. Single mothers bear dual responsibilities as primary caregivers and breadwinners, requiring strong adaptability, emotional resilience, and effective time management. Using a descriptive qualitative approach, this research explores the experiences of single mothers in providing attention, education, and emotional support to their children despite various limitations. The findings show that single mothers play a strategic role in shaping their children’s character, discipline, and independence. Although they often encounter economic pressures, psychological burdens, and limited social support, they continuously strive to create a stable and nurturing caregiving environment. Support from extended family, community, and social policies significantly strengthens their ability to fulfill these responsibilities. This study concludes that the role of single mothers is crucial to children’s development, and sustained social intervention is needed to help them carry out childcare more effectively.